Correlation of Temperature, pH and DO with Phytoplankton Abundance in the Maubesi River, East Nusa Tenggara - Priyambodo, Hernur Yoga; Santiari, Made; Amrulloh, Mohamad Fajar Farid (Bioedunis Journal, 2025)
Maubesi River is one of the rivers on Timor Island. Its clear water makes the river a source of water for the surrounding population. However, the condition of the river is unknown based on the presence of phytoplankton. Phytoplankton can be an indicator for these waters. This study aims to determine the effect of temperature, pH and DO on phytoplankton in these waters. The method used in determining the research station is purposive random sampling. The results of the study showed that the abundance of phytoplankton in the Maubesi River is relatively low, namely at 417 -1792 Ind / L and according to existing literature, based on its abundance, the Maubesi River is classified as Oligotrophic. Meanwhile, through simple linear regression analysis, the three environmental factors, namely Temperature, pH and DO, do not have a strong effect on the abundance of Phytoplankton, thus the abundance of Phytoplankton is influenced by other factors besides Temperature, pH and DO.